2013
DOI: 10.3329/seajph.v2i2.15961
|View full text |Cite
|
Sign up to set email alerts
|

Managing clinical trials in Asia: Issues, threats, opportunities and approaches

Abstract: not available DOI: http://dx.doi.org/10.3329/seajph.v2i2.15961 South East Asia J Public Health | Jul-Dec 2012 | Vol 2 Issue 2 | 80-84

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…[211] Asia is also the most populated continent in the world, with more than half of the world's population. [131415] In addition, the clinical trial cost in Asia is about 30%–40% lower than the USA and the EU,[2] with the combined cost for each patient per visit in China, India, and Thailand nearly equivalent to per patient per visit cost in the USA alone. [2]…”
Section: Discussionmentioning
confidence: 99%
“…[211] Asia is also the most populated continent in the world, with more than half of the world's population. [131415] In addition, the clinical trial cost in Asia is about 30%–40% lower than the USA and the EU,[2] with the combined cost for each patient per visit in China, India, and Thailand nearly equivalent to per patient per visit cost in the USA alone. [2]…”
Section: Discussionmentioning
confidence: 99%
“…High clinical trials cost, financial crises, limited patient pool, and other administrative expenses have prompted the study sponsors of North America and Western Europe to look for an alternative destination in order to cope with this dilemma. 6 It is prudent to conduct feasibility for clinical trials that eventually provides optimum results; it's not deemed viable to conduct a clinical trial without looking at the incidence of the target disease in a selected country. Likewise, Asian countries provides more study subjects for an oncology trials while the pool of an oncology patients have already been consumed in the west.…”
Section: Figure 1: Percentage Of Total Clinical Trials 31mentioning
confidence: 99%
“…In comparison to earlier data, there has been a decline in the total number of clinical studies in India, Thailand, Singapore, and Malaysia during the last 5 years; this decline trend is disconcerting which occurred due to the collective fall of phase 3 trials. 6 Fabricated data and uncertain regulatory environment have jolted India's clinical trial market despite of having an enormous potential for the recruitment of treatment naïve patients, thus prompting pharmaceutical companies to conduct clinical trials in other Asian countries. 10 The concept of four color light strategy was introduced by China Food and Drug Administration (CFDA) in 2015 that streamlined the drug approval process, thus encouraging sponsors to conduct clinical trials in China without facing delays in site initiation that usually occurs owing to lengthy ethical and regulatory approvals.…”
Section: Figure 1: Percentage Of Total Clinical Trials 31mentioning
confidence: 99%
“…In addition, with nearly 60% of the world population residing in Asia, countries within this region will be able to offer large and genetically diverse patient pools. This would complement the patient pools in occidental countries 9 . A recent review has examined the open‐access clinical trial registry clinicaltrials.gov for registered interventional recruiting early phase trials (Phase I/II) in the BRIC (Brazil, Russia, India, and China) countries and found that China accounted for 95% (842/888) of the trials; with gastrointestinal (17%, 148/888), lung (11%, 94/888), and breast (17%, 53/888) cancers being the most studied.…”
Section: Early Phase Oncology Clinical Trials In Asiamentioning
confidence: 99%
“…This would complement the patient pools in occidental countries. 9 A recent review has examined the open-access clinical trial registry clinicaltrials.gov for registered interventional recruiting early phase trials (Phase I/II) in the BRIC (Brazil, Russia, India, and China) countries and found that China accounted for 95% (842/888) of the trials; with gastrointestinal (17%, 148/888), lung (11%, 94/888), and breast (17%, 53/888) cancers being the most studied. This review has also highlighted that early phase trial testing in hematology and oncology has increased significantly throughout Asia, especially in China, which now has 18.5% of the global population.…”
mentioning
confidence: 99%